Déjà vecu for news events but not personal events: A dissociation between autobiographical and non-autobiographical episodic memory processing. (February 2017) - Turner, Martha S.; Shores, E. Arthur; Breen, Nora; Coltheart, Max
Abstract: In déjà vu, the feeling that what we are currently experiencing we have experienced before is fleeting and is not accepted as true. In contrast, in déjà vecu or "recollective confabulation", the sense of déjà vu is persistent and convincing, and patients genuinely believe that they have lived through the current moment at some previous time. In previous reports of cases of déjà vecu, both personal events and non-personal, world events gave rise to this experience. In this paper we describe a patient whose déjà vecu experiences are entirely restricted to non-personal events, suggesting that autobiographical and non-autobiographical episodic memory processing can dissociate. We suggest that this dissociation is secondary to differences in the degree to which personal and emotional associations are formed for these two different types of event, and offer a two-factor theory of déjà vecu.